(untitled) (GESTIÓN Y TENDENCIAS, 2021)
A number of reports warn of the consequences of both climate change and the prevailing pattern of global economic operation, which would reveal a set of negative externalities from 2030 onward. Taking that horizon into account, this paper proposes sustainability as a broader strategy, one that allows us to get ahead of scenarios that fall outside environmental regulation and to generate a resilient response to future impacts, bearing in mind that this dimension can already be discerned in emerging cases worldwide.